2016
DOI: 10.1155/2016/4315026
|View full text |Cite
|
Sign up to set email alerts
|

Application of Latitude Stripe Division in Satellite Constellation Coverage to Ground

Abstract: Grid point technique is a classical method in computing satellite constellation coverage to the ground regions. Aiming at improving the low computational efficiency of the conventional method, a method using latitude stripe division is proposed, which has high efficiency, and we name it latitude stripe method. After dividing the target region into several latitude stripes, the coverage status of each latitude stripe is computed by means of the spherical geometry relationship in the first orbital period. The lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…P and Q are the two intersection points. The longitude and latitude coordinates of P and Q can be computed by spherical geometry [27].…”
Section: Definition Of the Cell And Its Basic Properties The Definition Of Cell In This Paper Is As Followsmentioning
confidence: 99%
See 1 more Smart Citation
“…P and Q are the two intersection points. The longitude and latitude coordinates of P and Q can be computed by spherical geometry [27].…”
Section: Definition Of the Cell And Its Basic Properties The Definition Of Cell In This Paper Is As Followsmentioning
confidence: 99%
“…The spherical polygon division method [26] is based on the dual vino diagram of the spherical triangulation method, and it can be used to analyze arbitrarily shaped regions. The latitude band method [27] divides the target region into a group of latitude bands for analysis, and the algorithm is efficient. The feature area analysis method divides the two-dimensional sphere into a series of regions based on the trajectories of the satellites in the constellation [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown the possibility of using the Periodic Multi-Sun-Synchronous orbits (PMSSOs) for Earth and Mars observation; these orbits allow the observation of the same area under different solar illumination conditions and have a repetition period of the solar illumination conditions which is multiple of the repeat cycle [9,10]. Wang et al [14] divided the region by latitude stripes. The relationship between the cumulative coverage and the altitude can be quickly got, which is helpful for orbit designer to select optimal orbits for Earth observation.…”
Section: Introductionmentioning
confidence: 99%